A preliminary case series comparison of chest computerized tomography scan and Polymerase Chain Reaction (PCR) for COVID-19 contact tracing in developing countries with limited resources - Bahrami-Motlagh, Hooman; Papan, Amir Mohammad; Sahraei, Zahra; Salevatipour, Babak; Haghighimorad, Maryam; Karami, Alireza; Zaman, Mana; Radfar, Rastin; Shabani, Minoosh (Novelty in Biomedicine, 2022)
Background: Imaging and PCR each have a role in detecting and implementing precautionary measures in isolating individuals with a history of close contact, which helps limit the COVID-19 pandemic. Due to developing countries' difficulties, PCR is limited in Iran. This study seeks to determine the feasibility of early low-dose chest computed tomography (CT) scans substitution with PCR. Materials and Methods: Asymptomatic participants with a history of close contact with a confirmed case of COVID-19 were enrolled and followed for one week, receiving 2 PCR tests within one week. Initially, a chest CT scan was performed. The second CT scan was performed within one week on two participants. Participants with an initially negative CT scan and participants with a first CT scan compatible with COVID-19 who became symptomatic. Results: All Participants had an RT-PCR and at least one CT scan. Positive RT-PCR results were reported in 6 and 9 participants initially and within one week, respectively. Chest CT scans favoring COVID-19 infection were initially reported in 4 and 6 participants within one week, respectively. Seventeen participants showed neither symptoms nor positive RT-PCR or chested CT scans favoring COVID-19. Thirteen participants either had positive RT-PCR, a COVID-19 chest CT scan or became symptomatic. Conclusion: Rapid detection of COVID-19 and subsequent quarantining is crucial in the global fight against this pandemic. Our results showed lower sensitivity for chest CT scans compared to COVID-19 PCR, suggesting that chest CT scans are unsuitable for COVID-19 PCR tests.